Elevated nerve growth factor and neurotrophin-3 levels in cerebrospinal fluid of children with hydrocephalus - Hochhaus, Frederike (BioMed Central, 2001)
BACKGROUND: Elevated intracranial pressure (ICP) resulting from impaired drainage of cerebrospinal fluid (CSF) causes hydrocephalus with damage to the central nervous system. Clinical symptoms of elevated intracranial pressure (ICP) in infants may be difficult to diagnose, leading to delayed treatment by shunt placement. Until now, no biochemical marker of elevated ICP has been available for clinical diagnosis and monitoring. In experimental animal models, nerve growth factor (NGF) and neurotrophin-3 (NT-3) have been shown to be produced by glial cells as an adaptive response to hypoxia. We investigated whether concentrations of NGF and NT-3 are increased in the CSF of children with hydrocephalus. METHODS: NGF was determined in CSF samples collected from 42 hydrocephalic children on 65 occasions (taps or shunt placement surgery). CSF samples obtained by lumbar puncture from 22 children with suspected, but unconfirmed bacterial infection served as controls. Analysis was performed using ELISA techniques. RESULTS: NGF concentrations in hydrocephalic children were over 50-fold increased compared to controls (median 225 vs 4 pg/mL, p < 0.0001). NT-3 was detectable (> 1 pg/mL) in 14/31 hydrocephalus samples at 2–51 pg/mL but in none of 11 control samples (p = 0.007). CONCLUSION: NGF and NT-3 concentrations are increased in children with hydrocephalus. This may represent an adaptive response of the brain to elevated ICP.